MWCNT/rGO/natural rubber latex dispersions for innovative, piezo-resistive and cement-based composite sensors - L. Verdolotti (Nature Portfolio, 2021)
Abstract The present study is focused on the development and characterization of innovative cementitious-based composite sensors. In particular, multifunctional cement mortars with enhanced piezoresistive properties are realized by exploiting the concept of confinement of Multiwall Carbon Nanotubes (MWCNTs) and reduced Graphene Oxide (rGO) in a three-dimensional percolated network through the use of a natural-rubber latex aqueous dispersion. The manufactured cement-based composites were characterized by means of Inelastic Neutron Scattering to assess the hydration reactions and the interactions between natural rubber and the hydrated-cement phases and by Scanning Electron Microscopy and X-Ray diffraction to evaluate the morphological and mineralogical structure, respectively. Piezo-resistive properties to assess electro-mechanical behavior in strain condition are also measured. The results show that the presence of natural rubber latex allows to obtain a three-dimensional rGO/MWCNTs segregate structure which catalyzes the formation of hydrated phases of the cement and increases the piezo-resistive sensitivity of mortar composites, representing a reliable approach in developing innovative mortar-based piezoresistive strain sensors.